Antimicrobial and antibiofilm activity of biopolymer-Ni, Zn nanoparticle biocomposites synthesized using R. mucilaginosa UANL-001L exopolysaccharide as a capping agent - Garza-Cervantes, Javier Alberto (Int J Nanomedicine, 2019)
Introduction: Global increase in the consumption of antibiotics has induced selective stress on wild-type microorganisms, pushing them to adapt to conditions of higher antibiotic concentrations, and thus an increased variety of resistant bacterial strains have emerged. Metal nanoparticles synthesized by green methods have been studied and proposed as potential antimicrobial agents against both wild-type and antibiotic-resistant strains; in addition, exopolysaccharides have been used as capping agent of metal nanoparticles due to their biocompatibility, reducing biological risks in a wide variety of applications. Purpose: In this work, we use an exopolysaccharide, from Rhodotorula mucilaginosa UANL-001L, an autochthonous strain from the Mexican northeast, as a capping agent in the synthesis of Zn, and Ni, nanoparticle biopolymer biocomposites. Materials and methods: To physically and chemically characterize the synthesized biocomposites, FT-IR, UV-Vs, TEM, SAED and EDS analysis were carried out. Antimicrobial and antibiofilm biological activity were tested for the biocomposites against two resistant clinical strains, a Gram-positive Staphylococcus aureus, and a Gram-negative Pseudomonas aeruginosa. Antimicrobial activity was determined using a microdilution assay whereas antibiofilm activity was analyzed through crystal violet staining. Results: Biocomposites composed of exopolysaccharide capped Zn and Ni metal nanoparticles were synthesized through a green synthesis methodology. The average size of the Zn and Ni nanoparticles ranged between 8 and 26 nm, respectively. The Ni-EPS biocomposites showed antimicrobial and antibiofilm activity against resistant strains of Staphylococcus aureus and Pseudomonas aeruginosa at 3 and 2 mg/mL, respectively. Moreover, Zn-EPS biocomposites showed antimicrobial activity against resistant Staphylococcus aureus at 1 mg/mL. Both biocomposites showed no toxicity, as renal function showed no differences between treatments and control in the in vivo assays with male rats tests in this study at a concentration of 24 mg/kg of body weight. Conclusion: The exopolysaccharide produced by Rhodotorula mucilaginosa UANL-001L is an excellent candidate as a capping agent in the synthesis of biopolymer-metal nanoparticle biocomposites. Both Ni and Zn-EPS biocomposites demonstrate to be potential contenders as novel antimicrobial agents against both Gram-negative and Gram-positive clinically relevant resistant bacterial strains. Moreover, Ni-EPS biocomposites also showed antibiofilm activity, which makes them an interesting material to be used in different applications to counterattack global health problems due to the emergence of resistant microorganisms.